Diseño de una máquina asentadora de válvulas para culatas con cuatro válvulas por cámara en la rectificación y reparación de motores de combustión interna (2023)
In this document, a valve seating machine is designed where mention is made of valve seating in internal combustion engines, the materials necessary to carry out this process, and the different techniques used. For the parameterization of the machine, the rotation speeds and force applied to the valves at the time of seating are taken into account. Different cylinder head geometries are also characterized, obtaining features such as length, width, height, among others that are necessary for the parameterization of the machine. the machine, different existing tools are chosen for the design and different design calculations are made to establish the maximum loads supported by the structure of the machine and finally reference is made to the roughness and shape changes in the seated valves and as this could improve the hermetic seal in the internal combustion chamber of an engine.